Evaluation of concurrent benzodiazepine and opioid prescribing patterns with a focus on acute muscle spasms indication at hospital discharge - Danielle Firkus; Krina Vyas; Jenna K. Lovely; Elaine Macon; Julie Cunningham (Surgery in Practice and Science, 2022)
Background: In 2016, the CDC Guidelines for Prescribing Opioids in Chronic Pain recommended avoiding the co-prescribing of opioids and benzodiazepines when possible. This evaluation provides one institution's approach to improve safety for new, acute concurrent opioid and benzodiazepine prescribing. Methods: Patients prescribed new, concurrent opioids and benzodiazepines upon discharge within one organization were identified. A chart review for the highest prescribing specialties was completed for a random sample of 100 patients to determine indications for prescribing, safety measures, and post discharge healthcare utilization. Results: Orthopedic surgery, the hospitalist service, neurosurgery, and general surgery had the highest concurrent prescribing rates. The most common indication for benzodiazepine prescribing was muscle spasms, but quantity variability existed across and within all four specialties. Of the subset of patients reviewed, patients were consistently not prescribed naloxone. Conclusions: A prescribing guideline was implemented to provide educational tools, standardized benzodiazepine quantities, and naloxone co-prescribing recommendations for the indication of muscle spasms.